Upaya Meningkatkan Prestasi Belajar Mahasiswa dengan Menggunakan Metode Montessori dalam Pembelajaran Daring pada Mata Kuliah Media Pembelajaran Prodi PAI IAIN Surakarta - Hakim, Pratiwi Rahmah (Universitas Nusantara PGRI Kediri, 2020)
The purpose of this study was to determine the efforts of lecturers in improving student achievement by using the Montessori method in online learning in the learning media course. This type of research is classroom action research or Crassroom Action Research (CAR). The place of this research is in the PAI IAIN Surakarta study program. The research time is from March 2020 to May 2020. The results obtained in this study show that the application of the Montessori method can improve student learning achievement in the learning media course of the PAI IAIN Surakarta Study Program. This can be seen in the percentage of test completeness in each competency. In the pre-cycle completeness of 17%, the first cycle of completeness of 46% and the second cycle of 97%.